Shale strata development problems and origin of the Bazhenov Formation fractures in the southeast of the West Siberian Plate; Russian Geology and Geophysics; Vol. 59, iss. 1 - Belozerov V. B. Vladimir Borisovich (2018, 2018)
Title screen